The Influence of Public Accounting Firm Reputation and Audit Report Lag on Company Value - Azhari Atul Aini; Yeni Tata Rini (Universitas Islam Sultan Agung, Faculty of Economic and Business, Accounting Dept, 2024)
Evaluating and studying how the reputation of the Public Accounting Firm (Kantor Akuntan Publik/KAP) and audit report lag affect firm value is the purpose of this research. On the other hand, this study also analyzes how value Earnings Per Share (EPS) is able to moderate the influence of the reputation of the Public Accounting Firm (Kantor Akuntan Publik/KAP) and audit report lag on firm value. This study uses a quantitative approach with the company's financial statements as secondary data. The population used is LQ45 companies on the Indonesia Stock Exchange in 2021-2022. From the population, 26 companies were selected as samples through purposive sampling. The data was tested using descriptive statistical analysis, linear regression analysis, and moderation test with the residual method. The study results reveal that the reputation of the KAP affects firm value, audit report lag does not affect firm value, EPS cannot moderate the effect of the reputation of the KAP on firm value, and EPS cannot moderate the effect of audit report lag on firm value.